1990
DOI: 10.1152/ajpheart.1990.258.2.h490
|View full text |Cite
|
Sign up to set email alerts
|

Ejection- and isovolumic contraction-phase wall thickening in nonischemic myocardium during coronary occlusion

Abstract: During acute regional ischemia in open-chest anesthetized dogs, contraction is augmented in nonischemic myocardium. The effectiveness of enhanced contraction, however, has been questioned based on recent studies (using midwall segment length measurements) that reported that most of the increase occurred only during the isovolumic contraction phase (ICP) and not the ejection phase (EP) of systole. We evaluated this issue retrospectively using a different means of measuring regional myocardial function, systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…It has been postulated that, during regional ischemia, either a difference in contractility (''weak and strong muscles in series'') or a difference in timing (''asynchrony'') between ischemic and nonischemic regions is responsible for the mechanical interaction (2,16,17,20,23,28). In the present study, we confirmed a role for both mechanisms in regionally stunned myocardium.…”
Section: Underlying Mechanismsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been postulated that, during regional ischemia, either a difference in contractility (''weak and strong muscles in series'') or a difference in timing (''asynchrony'') between ischemic and nonischemic regions is responsible for the mechanical interaction (2,16,17,20,23,28). In the present study, we confirmed a role for both mechanisms in regionally stunned myocardium.…”
Section: Underlying Mechanismsupporting
confidence: 85%
“…During ischemia, three independent factors have been identified to contribute to mechanical interaction: 1) changes in sympathetic tone, 2) the Frank-Starling mechanism, and 3) direct myocardial unloading (2,7,8,10,12,16,17,20,23,28,30). The proposed mechanism to explain mechanical interaction during ischemia is discussed for the present experimental conditions.…”
Section: Underlying Mechanismmentioning
confidence: 83%
“…37 Apart from NOS-derived NO, we have recently demonstrated NOS-independent NO accumulation within the myocardial interstitium during myocardial ischemia in vivo. 38 Although NOS-independent NO production may thus have contributed to nitrite formation during ischemia, cellular contractile dysfunction triggered by L-arginine in ISCH was reversible by iNOS inhibition, suggesting that iNOSdependent NO formation confined to the cardiomyocyte was most important for the measured functional alterations.…”
Section: Discussionmentioning
confidence: 97%
“…physiologic vs. pathologic) and magnitude of the resultant cardiac hypertrophy have not been reported. Abrupt occlusion of a coronary artery in mammals leads to myocardial infarction and hypertrophy of the remaining viable tissue that is phenotypically pathological (13)(14)(15). It is not clear, however, whether gradual LCX occlusion stimulates changes in gene expression that are associated with the physiological or pathological phenotype.…”
Section: Introductionmentioning
confidence: 99%